(untitled) (Research Journal of Mathematics & Technology, 2022)
This article explores the use of wikis to support student inquiry in large classes. The traditional tools of inquiry-based learning, such as group work and in-class presentations, are described and their applicability to large classes is assessed. Online learning management systems, and Wikis in particular, can help to address issues of scale and meet instructor needs. Wikis offer a unique collaborative space for writing, and this article surveys the uses and benefits of wikis. In particular, issues of anonymity, stereotype threat, and inclusivity are addressed. These observations were made while using MediaWiki to support student inquiry in a multivariable calculus course.